2012
DOI: 10.1371/journal.pone.0037534
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Sensorimotor Cortical Oscillations during the Observation of Hand Movements: An EEG Study

Abstract: BackgroundThe observation of action done by others determines a desynchronization of the rhythms recorded from cortical central regions. Here, we examined whether the observation of different types of hand movements (target directed, non-target directed, cyclic and non-cyclic) elicits different EEG cortical temporal patterns.MethodologyVideo-clips of four types of hand movements were shown to right-handed healthy participants. Two were target directed (grasping and pointing) motor acts; two were non-target dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
127
3
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(167 citation statements)
references
References 58 publications
31
127
3
3
Order By: Relevance
“…The dorsolateral prefrontal cortex is activated when movements that match normal human movements are observed [31]. Previous studies have also shown that the mu ERD value for the sensorimotor regions increases during the observation of hand movements [32][33][34][35]. These studies indicate that during the observation of the hammer movement, the subjects were observing the footage of others performing the action while mentally simulating the same action.…”
Section: Discussion Observationmentioning
confidence: 78%
“…The dorsolateral prefrontal cortex is activated when movements that match normal human movements are observed [31]. Previous studies have also shown that the mu ERD value for the sensorimotor regions increases during the observation of hand movements [32][33][34][35]. These studies indicate that during the observation of the hammer movement, the subjects were observing the footage of others performing the action while mentally simulating the same action.…”
Section: Discussion Observationmentioning
confidence: 78%
“…In our study, we found that the 20-25 Hz band is the most sensitive in both monkeys, and the magnitude of suppression is more robust in the anterior and central electrodes. Other work in humans has shown that during action observation, frequency bands within this range show similar desynchronization [3,11,30,34,37] rstb.royalsocietypublishing.org Phil. Trans.…”
Section: Discussionmentioning
confidence: 86%
“…It is possible that with EEG recordings, the observation of biological movements devoid of the target-object, which is known to involve temporoparietal -premotor networks, could produce EEG changes similar to those reported during observation of goal-directed movements. The work in humans has shown that meaningful and meaningless movements can induce desynchronization of the alpha rhythm [3,8,10,37]. Related to this point, it would be interesting to investigate whether actions with a tool, or objects moving with a biological kinematics towards a goal, are capable of eliciting a similar desynchronization.…”
Section: Discussionmentioning
confidence: 98%
“…Avanzini et al [25] investigated the dynamics of sensorimotor cortical oscillations during Understanding Neural Mechanisms of Action Observation for Improving Human Motor Skill... http://dx.doi.org/10.5772/intechopen.69266 5 the observation of hand movements using EEG (Figure 6). A desynchronization of alpha and beta rhythms was observed in the central and parietal regions.…”
Section: Mirror Neuron System and Eeg Studiesmentioning
confidence: 99%